Blue/red ratiometric pH sensors without background signals based on 808 nm-excited core–triple shell up-conversion nanoparticles. Issue 48 (25th November 2021) - Wang, Tao; Sun, Fenglei; Jiang, Zike; Wang, Jing; Ma, Yanyan; Lin, Haitao; Lv, Hongmin; Xu, Shanshan; Li, Jinhua; Zhou, Guangjun
Abstract : A pH sensor based on CTS UCNPs exhibits ratiometric responses from pH 4 to 7 according to blue/red luminescence intensity ratios under 808 nm excitation. Abstract : pH sensors based on up-conversion nanoparticles (UCNPs) are widely studied due to their effective elimination of background signals. However, ratiometric pH measurement depending on blue and red luminescence under NIR irradiation has been seldom reported for the lack of simultaneous strong blue and red emissions for traditional UCNPs. In this work, we designed NaGdF4 :Yb, Tm@NaYF4 :Yb, Eu@NaYF4 :Yb, Nd@NaYF4 core–triple shell (CTS) UCNPs as fluorescent materials to realize blue/red ratiometric pH measurement. On the basis of Gd 3+ -mediated interfacial energy transfer and Yb 3+ -mediated energy migration, CTS particles present intense luminescence and a high red/blue (615 nm/450 nm) peak intensity ratio of 0.47 at 808 nm excitation. Composed of these particles and pH indicator bromocresol green, the pH sensor exhibits ratiometric responses in a pH range of 4–7 according to blue/red luminescence intensity ratios, avoiding the common errors as well as potential mutual fluorescence signal interference. Owing to strong overall luminescence and additional red emission of CTS UCNPs distinctly improving the signal-to-noise ratio, this ratiometric sensor reveals high sensitivity. Moreover, the employed excitation wavelength of 808 nm can not only eliminate autofluorescence signals, but also alleviate severe temperature rise in biosamples under continuous irradiation, ensuring accurate pH determination. More intriguingly, a CCD RGB camera serves as a collector to record luminescence signals, further promoting commercial feasibility. The successful application of CTS UCNPs on sensors indeed realizes blue/red ratiometric measurement towards pH under 808 nm irradiation, also pointing out a novel way for pH sensors with high sensitivity and accuracy.